Expanding Participatory Data Analysis: An Innovative Strategy for Engaging Community Advisory Board (CAB) in Qualitative Research Data Analysis **Virtually** - Cirila Estela Vasquez Guzman; John Heintzman (Journal of Participatory Research Methods, 2024)
This brief provides an innovative and practical manner in which to better engage community advisory boards (CABs) with data analysis. A growing number of scholars are interested in better integrating the community into the data analysis of community based participatory research, community engaged, and/or participatory action research. Participatory data analysis with the community is a critical way diverse communities with lived expertise can inform analysis and interpretation of data grounded in community's voice, perspectives, and meanings. We describe the cervical cancer project, whereby a community advisory board (CAB) was integrated into qualitative data analysis starting by focusing on the codebook, an integral part of data analysis. This brief provides three specific ways in which participatory qualitative analysis can improve the manner in which research engages the community. We outline one opportunity for scholars to actively engage community partners virtually in the data analysis using the codebook with specific strategies to facilitate participation. We encourage researchers to consider these strategies for disruption when re-thinking the practice of CBPR especially during the analysis stage particularly when it comes to research with black, indigenous, and other people of color (BIPOC), under-represented, or marginalized communities with limited English, literacy and/or education levels.